2014
DOI: 10.3329/bjn.v30i1.57361
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of ECG findings in Ischemic Stroke

Abstract: Background: The diagnosis of ischemic stroke remains a clinical one, with confirmatory evidence obtained through neuroimaging. ECG changes are common in patients with ischemic stroke. Objective: The objective of this study was to see ECG findings among ischemic stroke patients. Materials and Methods: This study was carried out in the Department of Neurology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from July 2006 to October 2008. A total of 36 patients with acute Ischemic stroke were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…18 Islam et al, (2010)found that 20% of their patients with acute ischemic stroke were diabetic. 24 29 The development of post-stroke depression is probably multi-factorial. Where the lesion occur, inadequate social support, dependence to daily living activities and inability to perform previous activities can reduce persons quality of living and make him/her prone to psychiatric illness.…”
Section: Discussionmentioning
confidence: 99%
“…18 Islam et al, (2010)found that 20% of their patients with acute ischemic stroke were diabetic. 24 29 The development of post-stroke depression is probably multi-factorial. Where the lesion occur, inadequate social support, dependence to daily living activities and inability to perform previous activities can reduce persons quality of living and make him/her prone to psychiatric illness.…”
Section: Discussionmentioning
confidence: 99%